Cold-rolled steel sheet and hot-dip galvanized steel sheet with excellent workability, and manufacturing method thereof
A cold-rolled steel sheet with optimized alloy composition and controlled cooling process achieves high strength and workability by fine dispersion of martensite phases, addressing the limitations of existing high-strength steel sheets in automotive applications.
Patent Information
- Application Number
- JP2021534703
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2018-12-18
- Filing Date
- 2019-12-17
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2039-12-17
AI Technical Summary
Existing high-strength steel sheets face challenges in achieving both high tensile strength and good workability, with issues such as decreased elongation rates, cracks, and wrinkles during press-forming, particularly in automotive applications.
A cold-rolled steel sheet with a specific alloy composition and microstructure, including controlled ratios of elements like C, Si, Mn, Mo, Cr, and a balanced microstructure of ferrite, bainite, and martensite, combined with a controlled cooling process to achieve fine and uniform dispersion of martensite phases, enhancing work hardening and ductility.
The solution results in steel sheets with improved workability, preventing processing defects like cracks and wrinkles, allowing for complex shapes in automotive parts, while maintaining high strength and ductility.
Smart Images

Figure 0007611827000004 
Figure 0007611827000005 
Figure 0007611827000006
Abstract
Description
[Technical field]
[0001] The present invention relates to a high-strength cold-rolled steel sheet and hot-dip galvanized steel sheet having a tensile strength of 980 MPa or more, which are used mainly for automotive structural members, and to a method for producing the same. [Background technology]
[0002] In recent years, in the field of automotive steel sheets, there has been a demand for stronger steel sheets to improve fuel efficiency and durability in response to various environmental and energy use regulations, and from the viewpoint of impact safety and passenger protection, the amount of high-strength steel sheets with a tensile strength of 980 MPa or more used for car body structures and reinforcement materials has been increasing. In particular, as the regulations on impact stability for automobiles have expanded recently, high-strength steels with excellent yield strength have been adopted for structural members such as members, seat rails, and pillars in order to improve the impact resistance of the car body.
[0003] Conventional methods for strengthening steel include solid solution strengthening, precipitation strengthening, strengthening by grain refinement, transformation strengthening, etc. However, among the above methods, solid solution strengthening and strengthening by grain refinement have the disadvantage that it is very difficult to manufacture high-strength steel with a tensile strength of 590 MPa or more.
[0004] Precipitation-hardened high-strength steel is a technology that ensures strength by adding carbonitride-forming elements such as Cu, Nb, Ti, and V to precipitate carbonitrides to strengthen steel sheets, or by miniaturizing grains by suppressing grain growth due to fine precipitates. The above technology has the advantage of being able to easily obtain high strength at low manufacturing costs. However, it has the disadvantage that high-temperature annealing must be performed to cause sufficient recrystallization and ensure ductility, since the recrystallization temperature rises rapidly due to fine precipitates. In addition, precipitation-hardened steel, which is strengthened by precipitating carbonitrides in the ferrite matrix, has the problem that it is difficult to obtain high-strength steel of 600 MPa class or more.
[0005] In addition, various transformation-strengthened high-strength steels have been developed, such as ferrite-martensite dual-phase steels that contain hard martensite in the ferrite matrix, transformation-induced plasticity (TRIP) steels that utilize the transformation-induced plasticity of retained austenite, and complex phase (CP) steels that are composed of ferrite and hard bainite or martensite structures.
[0006] However, in general, as the strength of steel sheet increases, the elongation decreases, which causes a problem of reduced formability. Therefore, as the strength is increased, cracks and wrinkles occur during the press forming of automobile parts, which limits the production of complex parts.
[0007] An example of a conventional technique for improving the workability of the high-tensile steel sheet is the invention disclosed in Patent Document 1. Patent Document 1 discloses a method for producing a high-tensile steel sheet having a composite structure mainly composed of martensite, in which fine precipitated copper particles having a particle size of 1 to 100 nm are dispersed inside the structure to improve the workability. However, the technique of Patent Document 1 has problems in that the Cu content is excessively added at 2 to 5% in order to precipitate good and fine Cu particles, which may cause red brittleness due to Cu, and the production cost increases excessively.
[0008] On the other hand, Patent Document 2 presents a precipitation hardened steel sheet having a ferrite matrix structure, a fine structure containing 2 to 10 area % of pearlite, and improved strength by precipitation hardening and grain refinement through the addition of carbonitride forming elements such as Nb, Ti, V, etc. However, the precipitation hardened steel sheet of Patent Document 2 has good hole expandability, but there is a limit to how much tensile strength can be increased, and it has a problem that cracks occur during press forming due to its high yield strength and low ductility.
[0009] In addition, Patent Document 3 provides a method for manufacturing a cold-rolled steel sheet that utilizes tempered martensite to simultaneously obtain high strength and high ductility and has an excellent sheet shape after continuous annealing. However, the cold-rolled steel sheet of Patent Document 3 has a high carbon content of 0.2% or more, which causes problems such as reduced weldability and the possibility of dents occurring in the furnace due to the large amount of Si contained. [Prior art documents] [Patent documents]
[0010] [Patent Document 1] JP 2005-264176 A [Patent Document 2] Korean Patent Publication No. 2015-0073844 [Patent Document 3] JP 2010-090432 A Summary of the Invention [Problem to be solved by the invention]
[0011] An object of the present invention is to provide a cold-rolled steel sheet and a hot-dip galvanized steel sheet which are high in strength and excellent in workability, and a method for manufacturing the same.
[0012] The object of the present invention is not limited to the above-mentioned contents. A person having ordinary knowledge in the technical field to which the present invention belongs will have no difficulty in understanding the further object of the present invention from the general matters of the specification of the present invention. [Means for solving the problem]
[0013] One aspect of the present invention is an alloy having, by weight percent, carbon (C): 0.06 to 0.15%, silicon (Si): 1.2% or less (excluding 0), manganese (Mn): 1.7 to 2.7%, molybdenum (Mo): 0.15% or less (excluding 0), chromium (Cr): 1.0% or less (excluding 0), phosphorus (P): 0.1% or less (excluding 0), sulfur (S): 0.01% or less (excluding 0), titanium (Ti): 0.001 to 0.04%, niobium (Nb): 0.001 to 0.04%, nitrogen (N): 0.01% or less (excluding 0), boron (B): 0.01% or less (excluding 0), the balance being Fe and This cold-rolled steel sheet has excellent workability and contains other unavoidable impurities. The contents of silicon (Si), carbon (C), manganese (Mn), molybdenum (Mo), and chromium (Cr) in the base structure at 1 / 4t of the thickness satisfy the following relational expression 1. The microstructure is composed, in area percentage, of 10-70% ferrite, 10-50% total of bainite and retained austenite, and the remainder fresh martensite. The ratio (Mb / Mt) of the total fraction of fresh martensite (Mt) to the fraction of fresh martensite (Mb) adjacent to bainite is 60% or more.
[0014] [Equation 1] ([Si]+[C]×3) / ([Mn]+[Mo]+[Cr])≧0.18 (Here, [Si], [C], [Mn], [Mo], and [Cr] are the weight percentages of silicon (Si), carbon (C), manganese (Mn), molybdenum (Mo), and chromium (Cr) at the 1 / 4t point of the thickness of the cold-rolled steel plate.)
[0015] The cold rolled steel sheet may further contain, by weight percent, aluminum (sol. Al): 1.0% or less (excluding 0), and antimony (Sb): 0.05% or less (excluding 0).
[0016] The cold-rolled steel sheet may have a ratio (Msm / Mt) of the total fraction of fresh martensite (Mt) to the fraction of fine fresh martensite (Msm) having an average grain size of 3 μm or less of 60% or more.
[0017] The cold rolled steel sheet can satisfy the following Relational Expression 2 in terms of work hardening index (n), elongation (El), tensile strength (TS), and yield ratio (YR), each measured in a deformation range of 4 to 6%. [Equation 2] n×El×TS / YR≧2500
[0018] Another aspect of the present invention is a hot-dip galvanized steel sheet comprising the above cold-rolled steel sheet on a surface of which a hot-dip galvanized layer is formed.
[0019] Another aspect of the present invention is a galvannealed steel sheet comprising the above-mentioned cold-rolled steel sheet on a surface of which a galvannealed layer is formed.
[0020] Another aspect of the present invention is a method for producing a steel slab containing, by weight percent, 0.06-0.15% carbon (C), 1.2% or less silicon (Si) (except 0), 1.7-2.7% manganese (Mn), 0.15% or less molybdenum (Mo) (except 0), 1.0% or less chromium (Cr) (except 0), 0.1% or less phosphorus (P) (except 0), 0.01% or less sulfur (S) (except 0), 0.001-0.04% titanium (Ti), 0.001-0.04% niobium (Nb), 0.01% or less nitrogen (N) (except 0), 0.01% or less boron (B) (except 0), the balance being Fe and other unavoidable impurities, the method comprising the steps of reheating the steel slab and hot rolling the slab so that the temperature at the finish rolling outlet side is Ar3 to Ar3+50°C; coiling the hot-rolled steel sheet at 400 to 700°C after the hot-rolling step, and then cooling the steel sheet from the coiling temperature to room temperature at an average cooling rate of 0.1°C / s or less to obtain a hot-rolled steel sheet; cold rolling the coiled hot-rolled steel sheet at a rolling reduction of 40 to 70% to obtain a cold-rolled steel sheet; annealing the cold-rolled steel sheet at an annealing temperature range of Ac1+20°C to Ac3-20°C; subjecting the annealed cold-rolled steel sheet to a primary cooling end temperature of 630 to 670°C from the annealing temperature at an average cooling rate of 10°C / s or less; performing second cooling from the first cooling end temperature to a second cooling end temperature range of 400 to 500°C at an average cooling rate of 5°C / s or more using a quenching device; After the secondary cooling, maintaining the secondary cooling end temperature for 70 seconds or more; and After the above-mentioned holding, a third cooling step is performed from the above-mentioned holding temperature to a temperature of Ms to 100°C or less at an average cooling rate of 5°C / s or more; The present invention relates to a method for producing a cold-rolled steel sheet having excellent workability, comprising the steps of:
[0021] The steel slab may further contain, by weight percent, aluminum (sol. Al): 1.0% or less (excluding 0), and antimony (Sb): 0.05% or less (excluding 0).
[0022] The continuous annealing can be carried out in a temperature range of 760 to 820°C.
[0023] After the tertiary cooling, the method may further include a step of performing temper rolling at a reduction rate of less than 1%.
[0024] Another aspect of the present invention is a method for producing a hot-dip galvanized steel sheet having excellent workability, further comprising a step of performing a hot-dip galvanizing treatment in a temperature range of 430 to 490°C after the holding step and before the tertiary cooling.
[0025] Another aspect of the present invention is a method for producing a galvannealed steel sheet having excellent formability, further comprising the step of performing an alloying heat treatment after the step of performing the galvanizing treatment and before the tertiary cooling. Effect of the Invention
[0026] According to the present invention, by optimizing the alloy composition and manufacturing process of the steel sheet, it is possible to provide a cold-rolled steel sheet and a hot-dip galvanized steel sheet that have a low yield ratio, which is a characteristic of DP steel, while having excellent elongation (El) and work hardening index (n) compared to DP steel.
[0027] By using the cold rolled steel sheet and hot-dip galvanized steel sheet according to the present invention, processing defects such as cracks and wrinkles that occur during press forming can be prevented, and therefore, the cold rolled steel sheet and hot-dip galvanized steel sheet can be used in a variety of automotive structural parts having complex shapes that require a wide range of processability, and have the advantage that the material properties and plating properties can be secured at the same time.
[0028] The various and beneficial advantages and effects of the present invention are not limited to the above-mentioned contents, but can be more easily understood in the course of describing specific embodiments of the present invention. [Brief description of the drawings]
[0029] [Figure 1] This shows the change in the occupancy ratio (Mb / Mt) of fresh martensite adjacent to bainite to the entire fresh martensite, according to Relation 1 ((Si+C×3) / (Mn+Mo+Cr)). [Diagram 2] The graph shows the change in the occupancy ratio (Msm / Mt) of fine fresh martensite with an average grain size of 3 μm or less to the entire fresh martensite due to the above occupancy ratio (Mb / Mt). [Diagram 3] This shows the change in Relation 2 (n×El×TS / YR) due to the above occupancy ratio (Mb / Mt). [Figure 4] This shows the change in Relation 2 (n×El×TS / YR) due to the above occupancy ratio (Msm / Mt). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0030] The terminology used herein is for the purpose of referring to particular embodiments only and is not intended to limit the invention. As used herein, the singular forms "a," "an," and "the" include the plural forms unless the term clearly indicates to the contrary.
[0031] The meaning of "comprising" as used in the specification is to embody certain properties, regions, integers, steps, operations, elements, and / or components, and does not exclude the presence or addition of other certain properties, regions, integers, steps, operations, elements, components, and / or groups.
[0032] Unless otherwise specified, all terms, including technical and scientific terms, used herein have the same meaning as commonly understood by a person of ordinary skill in the art to which the present invention belongs. Terms defined in commonly used dictionaries are additionally interpreted as having a meaning consistent with the relevant technical literature and the presently disclosed content, and are not interpreted as ideal or very formal meanings unless defined.
[0033] The present inventors have focused on the fact that, as one aspect of improving the workability of high strength steel, if it is possible to improve the elongation (El) and work hardening exponent (n) compared to DP steel while satisfying the yield ratio (YR), as in the properties of DP steel, which is the most widely used of transformation strengthened high strength steels, then processing defects such as cracks and wrinkles that occur during press forming can be prevented, and the application of high strength steels to complex parts can be expanded.
[0034] As a result of further intensive research, the inventors have found that when a small amount of bainite is introduced into the final microstructure of a cold-rolled steel sheet or a hot-dip galvanized steel sheet and fresh martensite is formed adjacent to the bainite, the fresh martensite is uniformly dispersed and its size is significantly refined, so that deformation can be effectively dispersed at the initial stage of forming, and the work hardening rate is significantly improved. In addition, it has been confirmed through experiments that when such a microstructure is provided, local stress concentration is alleviated and nucleation, growth, and coalescence of voids are delayed, thereby significantly improving ductility, and the present invention has been completed based on the experimental results.
[0035] Hereinafter, a cold-rolled steel sheet, a hot-dip galvanized steel sheet, and an alloyed hot-dip galvanized steel sheet having excellent workability according to one aspect of the present invention will be described in detail. It should be noted that in the present invention, when the content of each element is expressed, it means weight % unless otherwise specified. Furthermore, the proportion of crystals or texture is based on the area unless otherwise specified.
[0036] First, the chemical composition of the cold-rolled steel sheet having excellent workability according to one aspect of the present invention will be described. The cold-rolled steel sheet according to one aspect of the present invention contains, by weight percent, carbon (C): 0.06 to 0.15%, silicon (Si): 1.2% or less (excluding 0), manganese (Mn): 1.7 to 2.7%, molybdenum (Mo): 0.15% or less (excluding 0), chromium (Cr): 1.0% or less, phosphorus (P): 0.1% or less (excluding 0), sulfur (S): 0.01% or less (excluding 0), titanium (Ti): 0.001 to 0.04%, niobium (Nb): 0.001 to 0.04%, nitrogen (N): 0.01% or less (excluding 0), boron (B): 0.01% or less (excluding 0), the balance being Fe and other inevitable impurities.
[0037] Carbon (C): 0.06~0.15% Carbon (C) in steel is a very important element added to strengthen the transformation structure. C increases the strength and promotes the formation of martensite in dual-phase steel. When the C content increases, the amount of martensite in the steel increases. However, when the amount exceeds 0.15%, the strength of martensite increases, but the strength difference with ferrite, which has a low carbon concentration, increases. Due to such a strength difference, fracture is likely to occur at the interphase interface when stress is applied, and ductility and work hardening rate decrease. In addition, weldability decreases, so there is a possibility that welding defects will occur during part processing. On the other hand, if the C content is low at 0.06% or less, it may be extremely difficult to ensure the desired strength. Therefore, in the present invention, the C content is preferably limited to 0.06 to 0.15%, and in some cases, it can be limited to 0.06 to 0.12%.
[0038] Silicon (Si): 1.2% or less (excluding 0) The silicon (Si) is a ferrite stabilizing element, which promotes ferrite transformation and promotes C concentration in untransformed austenite, thereby contributing to the formation of martensite. It also has good solid solution strengthening ability, is effective in increasing the strength of ferrite and reducing the hardness difference between phases, and is a useful element that can ensure strength without reducing the ductility of the steel sheet. However, if the Si content exceeds 1.2%, it may induce surface scale defects, deteriorate the surface quality of the plating, and deteriorate the chemical conversion treatability. Therefore, in the present invention, the Si content is preferably limited to 1.2% or less (excluding 0), and in some cases may be limited to 1.0% or less (excluding 0).
[0039] Manganese (Mn): 1.7-2.7% Manganese (Mn) is an element that refines particles without damaging ductility, completely precipitates sulfur in steel as MnS, prevents hot embrittlement due to the formation of FeS, and strengthens steel. Mn also plays a role in lowering the critical cooling rate at which martensite phase is obtained in dual-phase steel, making martensite easier to form. In order to obtain the above effects and ensure the strength targeted in the present invention, the Mn content is preferably 1.7% or more. On the other hand, if the Mn content exceeds 2.7%, there is a high possibility that problems such as weldability and hot rolling properties will occur, martensite will be excessively formed, making the material unstable, and there is a high risk of processing cracks and plate breakage due to the formation of Mn oxide bands in the structure. In addition, there is a problem that Mn oxide dissolves on the surface during annealing, greatly impairing galvanic properties. Therefore, in the present invention, the Mn content is preferably limited to 1.7 to 2.7%, and can be limited to 1.8 to 2.5% in some cases.
[0040] Molybdenum (Mo): 0.15% or less (excluding 0) Molybdenum (Mo) is an element that is added to delay the transformation of austenite to pearlite, refine ferrite, and improve strength. Mo has the advantage of improving the hardening ability of steel and forming fine martensite at grain boundaries, making it possible to control the yield ratio. However, since Mo is an expensive element, it is preferable to appropriately control its content since the higher its content, the more disadvantageous it becomes in manufacturing. In order to obtain the above-mentioned effects, it is preferable to add Mo at a maximum of 0.15%. If the Mo content exceeds 0.15%, the alloy cost will increase sharply, the economy will decrease, and the ductility of the steel will decrease due to the excessive grain refinement effect and solid solution strengthening effect. Therefore, in the present invention, it is preferable to limit the Mo content to 0.15% or less (excluding 0).
[0041] Chromium (Cr): 1.0% or less (excluding 0) Chromium (Cr) is an element added to improve the hardening ability of steel and ensure high strength. It also plays a very important role in the formation of martensite, and is advantageous in the manufacture of dual-phase steel with high ductility because it minimizes the decrease in elongation compared to the increase in strength. In particular, Cr is added during the hot rolling process. 23 It forms Cr-based carbides such as C6, some of which dissolve during the annealing process and some of which remain undissolved, and can control the amount of solute C in martensite after cooling to an appropriate level or less, suppressing the occurrence of yield point elongation (YP-El), making it an advantageous element for manufacturing dual-phase steel with a low yield ratio. However, if the Cr content exceeds 1.0%, not only does the effect saturate, but there is also a problem that the cold rolling property is reduced due to an excessive increase in hot rolling strength. In addition, the proportion of Cr-based carbides increases and coarsens, causing the size of martensite to coarsen after annealing, resulting in a problem of reduced elongation. Therefore, in the present invention, it is preferable to limit the Cr content to 1.5% or less.
[0042] Phosphorus (P): 0.1% or less Phosphorus (P) in steel is a substitutional element with the greatest effect of solid solution strengthening, and is the most advantageous element for improving in-plane anisotropy and ensuring strength without significantly impairing formability. However, if added in excess, there is a problem that the possibility of brittle fracture increases significantly, which may cause slab breakage during hot rolling, and that it acts as an element that inhibits the properties of the coating surface. Therefore, in the present invention, the P content is controlled to a maximum of 0.1%.
[0043] Sulfur (S): 0.01% or less Sulfur (S) is an unavoidable impurity element added to steel, and since it impairs ductility and weldability, it is important to control its content as low as possible. In particular, since it increases the possibility of generating red shortness, it is preferable to control its content to 0.01% or less.
[0044] Titanium (Ti): 0.001-0.04%, Niobium (Nb): 0.001-0.04% Titanium (Ti) and niobium (Nb) in steel are effective elements for increasing the strength of steel sheets and for refining crystal grains by forming nano-precipitates. When these elements are added, they combine with carbon to form very fine nano-precipitates, which strengthen the matrix structure and reduce the hardness difference between phases. If the Ti and Nb contents are less than 0.001%, it is difficult to ensure such effects, and if the contents exceed 0.04%, the manufacturing cost increases and the ductility may be significantly reduced due to excessive precipitates. Therefore, in the present invention, the Ti and Nb contents are preferably limited to 0.001 to 0.04%, and in some cases, the Ti and Nb contents may be limited to 0.001 to 0.03%, respectively.
[0045] Nitrogen (N): 0.01% or less Nitrogen (N) is an effective component for stabilizing austenite, but if its content exceeds 0.01%, there is a problem that the refining cost of steel rises sharply. In addition, the formation of AlN, etc., significantly increases the risk of cracks occurring during continuous casting, so it is preferable to limit its upper limit to 0.01%.
[0046] Boron (B): 0.01% or less (excluding 0) Boron (B) is a component that delays the transformation of austenite into pearlite during the cooling process during annealing, and is a hardening element that inhibits the formation of ferrite and promotes the formation of martensite. However, if the content exceeds 0.01%, excessive B will concentrate on the surface, which may lead to a decrease in plating adhesion, so the content is controlled to 0.01% or less.
[0047] According to one aspect of the present invention, the cold-rolled steel sheet having excellent workability may further contain, in addition to the above-mentioned components, aluminum (sol.Al): 1.0% or less (excluding 0), and antimony (Sb): 0.05% or less (excluding 0).
[0048] Aluminum (sol.Al): 1.0% or less (excluding 0) Acid-soluble aluminum (sol.Al) is an element added for grain refinement and deoxidation of steel, and is a ferrite stabilizing element like Si, and is an effective component for improving martensite hardening ability by distributing carbon in ferrite to austenite. It is also an effective element for effectively suppressing the precipitation of carbides in bainite when held in the bainite region, and improving the ductility of steel sheets. However, if the content of sol.Al exceeds 1.0%, although it is advantageous for increasing strength due to the grain refinement effect, there is a problem that not only the possibility of surface defects of plated steel sheets occurring due to excessive formation of inclusions during continuous casting operation of steelmaking is high, but also the manufacturing cost is increased. Therefore, in the present invention, it is preferable to control the content of sol.Al to 1.0%.
[0049] Antimony (Sb): 0.05% or less (excluding 0) Antimony (Sb) is an element that distributes in grain boundaries and retards the diffusion of oxidizing elements such as Mn, Si, and Al through the grain boundaries, and has an excellent effect of suppressing surface segregation of oxides and suppressing coarsening of surface segregated materials caused by temperature rise and changes in the hot rolling process. However, if the content exceeds 0.05%, not only does the effect saturate, but also the manufacturing cost and workability decrease, so the content is limited to 0.05% or less.
[0050] The remainder of the alloying elements is iron (Fe). However, in the normal manufacturing process, unintended impurities from the raw materials or the surrounding environment are inevitably mixed in, and it is not possible to exclude them. These impurities are known to anyone with ordinary skill in the art, so all of their contents will not be mentioned in detail.
[0051] Meanwhile, in the cold rolled steel sheet having excellent formability according to one aspect of the present invention, the contents of silicon (Si), carbon (C), manganese (Mn), molybdenum (Mo), and chromium (Cr) in the matrix structure at a thickness ¼ point may satisfy the following Relational Expression 1: [Equation 1] ([Si]+[C]×3) / ([Mn]+[Mo]+[Cr])≧0.18 (Here, [Si], [C], [Mn], [Mo], and [Cr] are the weight percentages of silicon (Si), carbon (C), manganese (Mn), molybdenum (Mo), and chromium (Cr) at the 1 / 4t point of the thickness of the cold-rolled steel sheet, respectively.)
[0052] In order to achieve the low yield ratio characteristic of DP steel and at the same time improve the work hardening rate and ductility compared to existing DP steels, it is essential to control the structure and components, and first of all, it is important to introduce a small amount of bainite into the microstructure. Such bainite reduces the hardness difference between the ferrite and martensite phases, and can further reduce the hardness difference between the phases by precipitating fine nano-sized precipitates in the ferrite.
[0053] Si is a ferrite stabilizing element, and contributes to the formation of martensite by promoting ferrite transformation and promoting C concentration in untransformed austenite. C also contributes to the formation and adjustment of the martensite fraction by promoting C concentration in untransformed austenite. On the other hand, Mn, Mo, and Cr are elements that contribute to improving hardenability, but their effect of contributing to C concentration in austenite is relatively low compared to Si and C. Therefore, it is important to properly adjust the ratios of Si, C, and other hardenable elements Mn, Mo, and Cr, and in the present invention, the appropriate ratios of these components are controlled by Relation 1.
[0054] In addition, when the relational expression 1 relating to the components of silicon (Si), carbon (C), manganese (Mn), molybdenum (Mo), and chromium (Cr) in the matrix structure at the thickness 1 / 4t point is controlled to 0.18 or more and the hot rolling and annealing operation conditions are optimized, a small amount of bainite can be introduced into the microstructure, and fresh martensite can be formed inside or adjacent to the bainite. Here, the adjacent surroundings of the bainite can be defined as a region within 1 μm from the boundary of the bainite phase. As shown in FIG. 1, when the value of the relational expression 1 is 0.18 or more, the occupancy ratio (Mb / Mt, hereinafter also referred to as "occupancy ratio (Mb / Mt)" or "ratio (Mb / Mt)") of fresh martensite adjacent to bainite in the entire fresh martensite in the microstructure can be secured to 60% or more. This also makes it possible to form an occupancy ratio (Msm / Mt, hereinafter also referred to as "occupancy ratio (Msm / Mt)" or "ratio (Msm / Mt)") of fine fresh martensite of 3 μm or less in the entire fresh martensite of 60% or more.
[0055] On the other hand, in the cold rolled steel sheet according to one aspect of the present invention, the microstructure may be composed of, in terms of area percent, 10 to 70% ferrite, 10 to 50% in total of bainite and retained austenite, and the remainder fresh martensite. If the ferrite structure is less than 10%, it is difficult to ensure elongation, and if the fraction exceeds 70%, it is difficult to ensure sufficient strength. In addition, the ratio (Mb / Mt) of the total fraction of fresh martensite (Mt) to the fraction of fresh martensite (Mb) adjacent to bainite may be 60% or more, and the ratio (Msm / Mt) of the total fraction of fresh martensite (Mt) to the fraction of fine fresh martensite (Msm) having an average grain size of 3 μm or less may be 60% or more. Here, the total fraction of fresh martensite (Mt) can be defined as the total fraction of fresh martensite in the microstructure of a steel material, and the fraction of fresh martensite adjacent to bainite (Mb) can be defined as the fraction of fresh martensite present in a region within a distance of 1 μm from bainite.
[0056] As described above, when the relational expression 1 is controlled to 0.18 or more and the hot rolling and annealing operation conditions are optimized according to the manufacturing method of the present invention, the occupancy ratio (Mb / Mt) of the fresh martensite adjacent to the bainite in the whole fresh martensite can be secured to be 60% or more as shown in FIG. 1. And, when the occupancy ratio (Mb / Mt) is 60% or more as shown in FIG. 2, fine fresh martensite of 3 μm or less is formed at an occupancy ratio (Msm / Mt) of 60% or more in the whole fresh martensite, and the phase can be finely and uniformly dispersed. This can suppress the formation of martensite bands that deteriorate the workability. However, if the occupancy ratio (Mb / Mt) is formed at less than 60%, the occupancy ratio (Msm / Mt) is low at less than 60%. As a result, a martensite band structure is formed, and the dispersion effect of fine fresh martensite disappears.
[0057] As mentioned above, in a composite structure in which the occupancy ratio (Mb / Mt) is precisely controlled to 60% or more and the occupancy ratio (Msm / Mt) is precisely controlled to 60% or more, each phase is finely and uniformly dispersed, the hardness difference between the phases is reduced, deformation begins at a low stress in the initial stage of plastic deformation, the yield ratio is low, and deformation is effectively dispersed, resulting in a high work hardening rate. In addition, such changes in the microstructure reduce the concentration of localized stress and deformation after necking, and delay the generation, growth, and coalescence of voids that cause ductile fracture, thereby improving the ductility of the steel. As a result, as shown in FIG. 3, when the occupation ratio (Mb / Mt) is controlled to 60% or more and the occupation ratio (Msm / Mt) is controlled to 60% or more, the following Relational Expression 2 regarding the work hardening exponent (n), elongation (El), tensile strength (TS), and yield ratio (YR) can be satisfied. In other words, it is possible to manufacture a cold-rolled steel sheet having excellent workability, in which the work hardening rate and ductility are significantly improved compared to existing DP steels while still satisfying the low yield ratio characteristic of DP steel.
[0058] [Equation 2] n×El×TS / YR≧2500 (Here, n, El, TS, and YR are the work hardening index (n), elongation (El), tensile strength (TS), and yield ratio (YR) measured in the deformation range of 4 to 6%, respectively.)
[0059] On the other hand, a hot-dip galvanized layer may be formed on the surface of a cold-rolled steel sheet having the above-mentioned alloy composition and microstructure, or an alloyed hot-dip galvanized layer may be formed by subjecting the hot-dip galvanized layer to alloying heat treatment.
[0060] Next, a method for producing a cold rolled steel sheet, a hot-dip galvanized steel sheet, and a hot-dip galvannealed steel sheet having excellent workability according to another aspect of the present invention will be described in detail.
[0061] A method for producing a cold-rolled steel sheet having excellent workability according to another aspect of the present invention includes the steps of reheating and hot-rolling a slab having the above-mentioned alloy composition, coiling and cooling to obtain a hot-rolled steel sheet, cold-rolling to obtain a cold-rolled steel sheet, continuous annealing, cooling after the continuous annealing (primary cooling, secondary cooling, holding, tertiary cooling), and temper rolling. In addition, after the holding step to obtain a hot-dip galvanized steel sheet or an alloyed hot-dip galvanized steel sheet, a hot-dip galvanizing treatment and, if necessary, an alloying heat treatment may be performed before the tertiary cooling.
[0062] Obtaining hot rolled steel sheets First, a steel slab having the above-mentioned alloy composition is prepared and reheated under general conditions. Slab reheating is a process for heating to facilitate the subsequent hot rolling and to obtain the desired physical properties of the steel sheet, and the present invention does not particularly limit the reheating conditions. However, as a non-limiting embodiment, the slab can be reheated in a temperature range of 1100 to 1300°C.
[0063] The reheated slab is finish hot rolled under normal conditions at a temperature equal to or higher than the Ar3 transformation point to obtain a hot rolled steel sheet. In the present invention, the hot rolling conditions are not particularly limited, and normal hot rolling conditions can be applied. However, as a non-limiting embodiment, hot rolling can be performed so that the temperature at the finish rolling outlet side is Ar3 to Ar3+50°C, and in some cases, hot rolling can be performed so that the temperature at the finish rolling outlet side is in the range of 800 to 1000°C.
[0064] The hot-rolled steel sheet subjected to the finish hot rolling can be coiled at 400 to 700°C, and then cooled from the coiling temperature to room temperature at an average cooling rate of 0.1°C / s or less. In this case, the average cooling rate can be defined as the average value of the cooling rate between the coiling temperature and room temperature. By satisfying the coiling temperature and cooling conditions, a hot-rolled steel sheet in which carbides that become austenite nucleation sites are finely dispersed in the base structure can be manufactured. When fine carbides are formed uniformly dispersed in the hot rolling process in this way, the carbides dissolve during the subsequent continuous annealing, forming finely dispersed austenite, and as a result, fine martensite can be uniformly dispersed after annealing.
[0065] Obtaining cold rolled steel sheets After the coiled hot-rolled steel sheet is pickled, it is cold-rolled at a rolling reduction of 40 to 70%. If the cold rolling reduction is less than 40%, it is difficult to ensure the target thickness, and furthermore, it may be difficult to correct the shape of the steel sheet. On the other hand, if the cold rolling reduction exceeds 70%, there is a high possibility that cracks will occur at the edge of the steel sheet, which will cause a problem of a load during cold rolling. Therefore, in the present invention, it is preferable to limit the cold rolling reduction to 40 to 70%.
[0066] Continuous annealing stage The cold-rolled steel sheet is subjected to continuous annealing in a temperature range of Ac1+20°C to Ac3-20°C. More preferably, continuous annealing can be performed in a temperature range of 760 to 820°C. The continuous annealing can also be performed in a continuous alloying hot-dip galvanizing continuous furnace. The continuous annealing is performed to form ferrite and austenite simultaneously with recrystallization and distribute carbon. If the continuous annealing temperature is less than Ac1+20°C or less than 760°C, sufficient recrystallization is not performed, and it is difficult to form sufficient austenite, making it difficult to ensure the target martensite and bainite fractions after annealing. On the other hand, if the temperature exceeds Ac3-20°C or 830°C, productivity decreases and excessive austenite is formed, and the bainite and martensite fractions increase significantly after cooling, increasing the yield strength, and the ductility decreases, making it difficult to ensure the low yield and high ductility characteristics that are the characteristics of DP steel. In addition, surface enrichment due to elements such as Si, Mn, and B that reduce the wettability of hot-dip galvanizing becomes severe, which may deteriorate the surface quality of the plating. In consideration of this, in the present invention, the continuous annealing temperature can be limited to a temperature range of Ac1+20°C to Ac3-20°C, and may be 760 to 820°C in some cases.
[0067] Cooling stage The continuously annealed steel sheet is primarily cooled from the continuous annealing temperature to a primary cooling end temperature range of 630 to 670°C at an average cooling rate of 10°C / s or less, and then secondarily cooled using quenching equipment from the primary cooling end temperature to a secondary cooling end temperature range of 400 to 500°C at an average cooling rate of 5°C / s or more to introduce bainite.
[0068] The primary cooling may be performed by slowly cooling at an average cooling rate of 10° C. / s or less, and the primary cooling end temperature may be in the range of 630° C. to 670° C. Here, the primary cooling end temperature may be defined as a time point at which quenching is started by further applying quenching equipment that has not been applied in the primary cooling.
[0069] The secondary cooling may be performed by quenching at an average cooling rate of 5°C / s or more, and the secondary cooling end temperature may be in the range of 400 to 500°C. The secondary cooling may be performed by further applying a quenching equipment not applied in the primary cooling, and preferably, a hydrogen quenching equipment using H2 gas may be used. At this time, it is important that the secondary cooling end temperature is controlled to 400 to 500°C at which bainite is effectively generated, but if it exceeds 500°C or is lowered to less than 400°C, it is difficult to obtain an effective bainite fraction, and the occupancy ratio of fresh martensite adjacent to bainite cannot be obtained to 60% or more. Therefore, it is not possible to obtain the occupancy ratio of fine fresh martensite of less than 3 μm to 60% or more, and as a result, the effect of refining and uniformly dispersing fresh martensite disappears, and the workability cannot be improved as desired.
[0070] Then, the material is held at the secondary cooling end temperature for 70 seconds or more to concentrate carbon in the untransformed austenite adjacent to the bainite, and then tertiary cooling is performed from the holding temperature to a temperature of Ms~100°C or less at an average cooling rate of 5°C / s or more, thereby introducing fine fresh martensite into the region adjacent to the bainite. Here, Ms means the transformation start temperature (°C) of martensite.
[0071] Furthermore, for the purpose of correcting the shape of the steel sheet after the tertiary cooling, temper rolling can be performed at a reduction rate of less than 1%.
[0072] Hot dip galvanizing and alloying heat treatment step On the other hand, after holding at the secondary cooling end temperature for 70 seconds or more and before the tertiary cooling, a hot-dip galvanizing treatment can be performed in a temperature range of 430 to 490° C. to form a hot-dip galvanized layer on the steel sheet. In addition, if necessary, an alloying heat treatment can be performed to form an alloyed hot-dip galvanized layer. EXAMPLES
[0073] The present invention will be described in more detail below with reference to examples. However, it should be noted that the following examples are intended to illustrate and embody the present invention, and are not intended to limit the scope of the present invention, since the scope of the present invention is determined by the matters described in the claims and matters that can be reasonably inferred therefrom.
[0074] (Example) First, a steel slab having the alloy composition (unit: wt.%) shown in Table 1 below was prepared, and then a cold-rolled steel sheet and a hot-dip galvanized steel sheet were produced under the production conditions shown in Table 2.
[0075] [Table 1]
[0076] [Table 2]
[0077] The mechanical properties, plating properties, and microstructural properties of each of the steel sheets manufactured as described above were evaluated, and the results are shown in Table 3 below. At this time, a tensile test for each test piece was performed in the L direction according to the ASTM standard to evaluate the tensile properties, and in particular, the work hardening rate was measured in the deformation rate range of 4 to 6% as specified in the VDA (German Automobile Association) standard.
[0078] The fraction of the microstructure was determined by analyzing the matrix structure at 1 / 4t of the plate thickness of the annealed steel plate. Specifically, after Nital corrosion, the fractions of ferrite (F), bainite (B), fresh martensite (Mt, Mb, Msm), and austenite (A) were measured using an FE-SEM and an image analyzer.
[0079] [Table 3]
[0080] As seen from Table 3 above, in Comparative Examples 1 to 5 in which the component ratios of the steel composition and the manufacturing process are outside the range of the present invention, or the internal structure fraction and occupancy ratio of the steel are outside the scope of the present invention, it can be confirmed that the value of Relational Formula 2 (n×El×TS / YR) is less than 2500, and the workability of the steel sheet targeted in the present invention cannot be ensured.
[0081] On the other hand, in the case of Examples 1 to 6, in which the range of components satisfies the requirements of the present invention and the microstructure satisfies the range of the present invention, the value of Relational Formula 2 (n×El×TS / YR) is as high as 2500 or more, which shows that the workability of the steel sheet targeted by the present invention can be ensured, and furthermore, the plating characteristics are also good.
[0082] Although the above description has been given with reference to the embodiments, it will be understood that a person skilled in the art can make various modifications and variations of the present invention without departing from the spirit and scope of the present invention as set forth in the claims below.
Claims
1. In weight percent, it consists of carbon (C): 0.06 to 0.15%, silicon (Si): 1.2% or less (excluding 0), manganese (Mn): 1.7 to 2.7%, molybdenum (Mo): 0.15% or less (excluding 0), chromium (Cr): 1.0% or less (excluding 0), phosphorus (P): 0.1% or less, sulfur (S): 0.01% or less, titanium (Ti): 0.001 to 0.04%, niobium (Nb): 0.001 to 0.04%, nitrogen (N): 0.01% or less, boron (B): 0.01% or less (excluding 0), with the balance being Fe and other unavoidable impurities. A cold-rolled steel sheet having excellent workability, in which the contents of silicon (Si), carbon (C), manganese (Mn), molybdenum (Mo) and chromium (Cr) in a base structure at a point of 1 / 4t thickness satisfy the following relational expression 1, the microstructure is composed of, in area percentage, 10 to 70% ferrite, 10 to 50% in total of bainite and retained austenite, and the remainder fresh martensite, and the ratio (Mb / Mt) of the total fraction of fresh martensite (Mt) to the fraction of fresh martensite (Mb) adjacent to bainite is 60% or more. [Relationship 1] ([Si]+[C]×3) / ([Mn]+[Mo]+[Cr])≧0.18 (Here, [Si], [C], [Mn], [Mo], and [Cr] are the weight percentages of silicon (Si), carbon (C), manganese (Mn), molybdenum (Mo), and chromium (Cr) at the 1 / 4t point of the thickness of the cold-rolled steel sheet, respectively.)
2. The cold-rolled steel sheet according to claim 1, further comprising, by weight percent, aluminum (sol. Al): 1.0% or less (excluding 0), and antimony (Sb): 0.05% or less (excluding 0).
3. 2. The cold rolled steel sheet according to claim 1, wherein a ratio (Msm / Mt) of a total fraction of fresh martensite (Mt) to a fraction of fine fresh martensite (Msm) having an average grain size of 3 μm or less is 60% or more.
4. The work hardening index (n), elongation (El), tensile strength (TS), and yield ratio (YR), each measured in a deformation range of 4 to 6%, satisfy the following Relational Formula 2. The cold-rolled steel sheet having excellent workability according to claim 1. [Relationship 2] n×El×TS / YR≧2500MPa%
5. A hot-dip galvanized steel sheet comprising the cold-rolled steel sheet according to claim 1 or 2, and a hot-dip galvanized layer formed on the surface of the cold-rolled steel sheet.
6. A galvannealed steel sheet comprising the cold rolled steel sheet according to claim 1 or 2, and a galvannealed layer formed on the surface of the cold rolled steel sheet.
7. A method for producing a cold-rolled steel sheet having excellent workability according to any one of claims 1 to 4, a step of reheating a steel slab consisting of, by weight percent, carbon (C): 0.06-0.15%, silicon (Si): 1.2% or less (excluding 0), manganese (Mn): 1.7-2.7%, molybdenum (Mo): 0.15% or less (excluding 0), chromium (Cr): 1.0% or less (excluding 0), phosphorus (P): 0.1% or less, sulfur (S): 0.01% or less, titanium (Ti): 0.001-0.04%, niobium (Nb): 0.001-0.04%, nitrogen (N): 0.01% or less, boron (B): 0.01% or less (excluding 0), the balance being Fe and other unavoidable impurities, and then hot rolling the steel slab so that the temperature at the finish rolling outlet side is Ar3 to Ar3+50°C; coiling the steel sheet at 400 to 700° C. after the hot rolling step, and then cooling the steel sheet from the coiling temperature to room temperature at an average cooling rate of 0.1° C. / s or less to obtain a hot-rolled steel sheet; cold rolling the coiled hot-rolled steel sheet at a rolling reduction of 40 to 70% to obtain a cold-rolled steel sheet; annealing the cold-rolled steel sheet in an annealing temperature range of Ac1+20°C to Ac3-20°C; subjecting the annealed cold-rolled steel sheet to a primary cooling end temperature of 630 to 670° C. from the annealing temperature at an average cooling rate of 10° C. / s or less; secondarily cooling the temperature from the first cooling end temperature to a second cooling end temperature range of 400° C. to 500° C. at an average cooling rate of 5° C. / s or more using a quenching device; After the secondary cooling, maintaining the secondary cooling end temperature for 70 seconds or more; and After the holding, a third cooling step is performed from the holding temperature to a temperature of Ms to 100° C. or less at an average cooling rate of 5° C. / s or more; A method for producing a cold-rolled steel sheet having excellent workability, comprising the steps of:
8. The steel slab further contains, by weight percent, aluminum (sol. Al): 1.0% or less (excluding 0), and antimony (Sb): 0.05% or less (excluding 0). The method for producing a cold-rolled steel sheet having excellent workability according to claim 7.
9. The method for producing a cold-rolled steel sheet having excellent workability according to claim 7, wherein the annealing is carried out at a temperature range of 760 to 820 ° C.
10. The method for producing a cold rolled steel sheet having excellent workability according to claim 7, further comprising the step of performing temper rolling at a rolling reduction of less than 1% after the tertiary cooling.
11. A method for producing a cold-rolled steel sheet with excellent workability as described in any one of claims 7 to 10, further comprising a step of performing a hot-dip galvanizing treatment in a temperature range of 430 to 490°C after the holding step and before the tertiary cooling.
12. A method for manufacturing an alloyed hot-dip galvanized steel sheet with excellent workability as described in claim 11, wherein an alloying heat treatment is performed after the hot-dip galvanizing treatment step and before the tertiary cooling step.
Citation Information
Patent Citations
High-strength steel having adequate workability and manufacturing method therefor
JP2005264176A
Super high-strength cold-rolled steel sheet excellent in ductility, and producing method of the same
JP2010090432A
KR2015-0073844